THE INFLUENCE OF PRODUCT KNOWLEDGE, RELIGIUSITY, HALAL AWARENESS OF PURCHASING DECISIONS ON HALAL PRODUCTS WITH ATTITUDE AS A MEDIATION VARIABLE - Silvia Fauziah; Nur Hidayah Al Amin (IAIN Surakarta, 2021)
The rapid economic development has an impact on the emergence of new companies that ultimately increase competition between companies. Including in the growing and expanding halal industry. In business competition in the halal industry, companies can not only focus on halal products, but also need to understand other factors that can influence consumer behavior towards halal products. This study aims to determine the influence of product knowledge, religiosity, halal awareness of purchasing decisions with attitudes as mediation variables.This study was conducted on Muslim communities in Surakarta region aged 15 years and above, and the sample was 100 respondents. The determination of samples wasÂ purposive sampling techniques and data collection methods by surveying using questionnaires with google form. This research used path analysis, and for data processing was conducted with IBM SPSS Statistics 25. The results of this research show that product knowledge, religiosity, halal awareness have a significant influence on attitudes. In addition, attitudes also have a significant influence on purchasing decisions. However, the attitude is not able to mediate religiosity and halal awareness of purchasing decisions.